Sustainable solid waste management from the perspective of strong regulation / Haidy Henry Dusim - Dusim, Haidy Henry (UiTM Cawangan Johor, 2019)
Despite the importance of the aspect of strong regulation towards a sustainable solid waste management system, there are still few studies focusing on analysing the sustainability of solid waste management from the perspective of strong regulation. Hence, this study aims to analyse the sustainability of the solid waste management system from the perspective of strong regulation. To conduct this study, Kota Kinabalu, Sabah was selected as a case study. Both qualitative and quantitative approaches were employed. The quantitative approach was mainly used to support the findings collected from the qualitative approach. Data collected were mainly through interviews, questionnaires and secondary data. Based on the overall findings, the study found that the sustainability of the existing solid waste management system in Kota Kinabalu, Sabah is still considered as unsustainable, as it still has weak regulation. This is reflected when the study found that the elements of strict enforcement and strict regulation in Kota Kinabalu were found to be less strict. Hence, the study suggests that to move towards a sustainable solid waste management system, it is important for the local government in Kota Kinabalu, Sabah to implement stricter enforcement and stricter regulation pertaining to its solid waste management.